DESKRIPSI KOMUNIKASI INTERPERSONAL PENDIDIK DALAM KEGIATAN BELAJAR MENGAJAR PADA PENDIDIKAN ANAK USIA DINI - Dicky Kurniawan (Universitas Negeri Padang, 2014)
Abstract This article is written to 1) See description of verbal interpersonal communication educators towards learners in the teaching and learning process in early childhood education, 2) see how the image of non-verbal interpersonal communication educators towards learners in the teaching and learning process in early childhood education. The research was conducted in PAUD Kecamatan Padang Barat the number of educators 34. Data collection techniques used were observation, data analysis techniques using a percentage formula. The results illustrate that 1) interpersonal communication is verbal communication is going well as aspects of language educators have used with good speech, educators using the polite speech, speech educators using the easy to understand the child, 2) nonverbal communication used by teachers in implement teaching and learning is going well dilhat of aspects of facial expressions educators looked at the kid in the face is good enough.